Re-examining the effect of wage delegation: a replication study of Charness et al. (2012) - Hendrik Niehoff; Philipp Schreck (Journal of Business Economics, 2024)
Experimental research has explored the effects of wage delegation on employee performance, with the pioneering attempt by (Charness et al., Am Econ Rev 102:2358–2379, 2012) in “The Hidden Advantage of Delegation: Pareto Improvements in a Gift Exchange Game”, published in the American Economic Review. We conducted a replication of their experiment for two main reasons: first, to validate the original findings that have influenced subsequent research, and second, to examine whether these results hold in contexts with reduced social proximity between workers and employers, a relevant issue due to the rise of remote work. Our online experiment, involving 410 participants, followed the original study's design but used a different sample. We successfully replicated the main finding that wage delegation increases employee effort, though the effect was smaller and largely due to employees granting themselves higher wages. These results support the notion that with decreasing social proximity, formal controls increase in importance.
Keywords: C91; J31; J33; J41; M52; 650; Wage delegation; Replication study; Performance incentives; Employee empowerment; Intrinsic motivation